Effects of implementing free maternity service policy in Kenya: an interrupted time series analysis - Evaline Lang'at; Lillian Mwanri; Marleen Temmerman (BMC, 2019)
Abstract Background Maternal and perinatal mortality is a major public health concern across the globe and more so in low and middle-income countries. In Kenya, more than 6000 maternal deaths, and 35,000 stillbirths occur each year. The Government of Kenya abolished user fee for maternity care under the Free Maternity Service policy, in June of 2013 in all public health facilities, a move to make maternity services accessible and affordable, and to reduce maternal and perinatal mortality. Method An observational retrospective study was carried out in 3 counties in Kenya. Six maternal health output indicators were observed monthly, 2 years pre and 2 years post- policy implementation. Data was collected from daily maternity registers in 90 public health facilities across the 3 counties all serving an estimated population of 3 million people. Interrupted Time Series Analysis (ITSA) with a single group was used to assess the effects of the policy. Standard linear regression using generalized least squares (gls) model, was used to run the results for each of the six variables of interest. Absolute and relative changes were calculated using the gls model coefficients. Results Significant sustained increase of 89, 97, and 98% was observed in the antenatal care visits, health facility deliveries, and live births respectively, after the policy implementation. An immediate and significant increase of 27% was also noted for those women who received Emergency Obstetric Care (EmONC) services in either the level 5, 4 and 3 health facilities. No significant changes were observed in the stillbirth rate and caesarean section rate following policy implementation. Conclusion After 2 years of implementing the Free Maternity Service policy in Kenya, immediate and sustained increase in the use of skilled care during pregnancy and childbirth was observed. The study suggest that hospital cost is a major expense incurred by most women and their families whilst seeking maternity care services and a barrier to maternity care utilization. Overall, Free Maternity Service policy, as a health financing strategy, has exhibited the potential of realizing the full beneficial effects of maternal morbidity and mortality reduction by increasing access to skilled care.